Formation of Chromophoric Dissolved Organic Matter by Bacterial Degradation of Phytoplankton-Derived Aggregates - Kinsey, Joanna D.; Corradino, Gabrielle; Ziervogel, Kai; Schnetzer, Astrid; Osburn, Christopher L. (Frontiers in Marine Science, 2018)
Organic matter produced and released by phytoplankton during growth is processed by heterotrophic bacterial communities that transform dissolved organic matter into biomass and recycle inorganic nutrients, fueling microbial food web interactions. Bacterial transformation of phytoplankton-derived organic matter also plays a poorly known role in the formation of chromophoric dissolved organic matter (CDOM) which is ubiquitous in the ocean. Despite the importance of organic matter cycling, growth of phytoplankton and activities of heterotrophic bacterial communities are rarely measured in concert. To investigate CDOM formation mediated by microbial processing of phytoplankton-derived aggregates, we conducted growth experiments with non-axenic monocultures of three diatoms (Skeletonema grethae, Leptocylindrus hargravesii, Coscinodiscus sp.) and one haptophyte (Phaeocystis globosa). Phytoplankton biomass, carbon concentrations, CDOM and base-extracted particulate organic matter (BEPOM) fluorescence, along with bacterial abundance and hydrolytic enzyme activities (α-glucosidase, β-glucosidase, leucine-aminopeptidase) were measured during exponential growth and stationary phase (~3-6 weeks) and following six weeks of POM degradation. Incubations were performed in rotating glass bottles to keep cells suspended, promoting cell coagulation and, thus, formation of macroscopic aggregates (marine snow), more similar to surface ocean processes. Maximum carbon concentrations, enzyme activities, and BEPOM fluorescence occurred during stationary phase. Net DOC concentrations (0.19-0.46 mg C L-1) increased on the same order as open ocean concentrations. CDOM fluorescence was dominated by protein-like signals that increased throughout growth and degradation becoming increasingly humic-like, implying the production of more complex molecules from planktonic-precursors mediated by microbial processing. Our experimental results suggest that at least a portion of open-ocean CDOM is produced by autochthonous processes and aggregation likely facilitates microbial reprocessing of organic matter into refractory DOM.